Highly abundant bacteria in the gut of Triatoma dimidiata (Hemiptera: Reduviidae) can inhibit the growth of Trypanosoma cruzi (Kinetoplastea: Trypanosomatidae) - Cambronero Heinrichs, Juan Carlos (2024)
Chagas disease, caused by the protozoan Trypanosoma cruzi, is a zoonosis primarily found in rural areas of Latin America. It is considered a neglected tropical disease, and Triatoma dimidiata is the main vector of the parasite in Central America. Despite efforts, Chagas disease continues to be a public health concern, and vector control remains a primary tool to reduce transmission. In this study, we tested the hypothesis that highly abundant bacteria in the gut of T. dimidiata inhibit the growth of T. cruzi. To achieve this, bacterial diversity in the gut of T. dimidiata specimens from Costa Rica was characterized by metabarcoding of the 16S rRNA, microbial isolation was performed, and the effect of freeze-dried supernatants of the isolates on T. cruzi was investigated. Metabarcoding showed that the most abundant genera in the gut were Corynebacterium, Tsukamurella, Brevibacterium, and Staphylococcus. Barcoding and sequences comparison confirmed that 8 of the 30 most abundant amplicon sequence variants (ASVs) were isolated, and 2 of them showed an inhibitory effect on the growth of T. cruzi epimastigotes. These bacteria correspond to isolates of Tsukamurella and Brevibacterium, which were respectively the second and sixth most abundant ASVs in the gut of T. dimidiata. Notably, only the isolate of Brevibacterium showed a significant difference in growth inhibition against epimastigotes of both T. cruzi strains tested. These findings suggest that the gut microbiota of T. dimidiata may play an active role in modulating parasite development.